2020
DOI: 10.1016/j.msard.2020.102512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the health care of >1,000 People living with multiple sclerosis: A cross-sectional study

Abstract: Background: People with multiple sclerosis (PwMS) experienced changes in health behaviors and access to MS care due to the COVID-19 pandemic. The USA has the highest recognized number of Covid19 infections globally. The extent of the impact of COVID-19 has not been well characterized in large samples of PwMS to date. The MS patient perspective on COVID-19 would complement the physician-reported cases of MS and COVID-19 in the literature. Methods: A cross-sectional survey of adult PwMS was performed online, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 19 publications
2
63
0
1
Order By: Relevance
“…Vogel et al reported that most patients with MS reported interruptions to their MS care and limited access to COVID-19 testing, which may have been the cause of this increase. 19 Woo et al reported that patients after COVID-19 recovery presented with substantial neurocognitive deficits related to attention, short-term memory and concentration and language tasks. 20 However, their cognitive status remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Vogel et al reported that most patients with MS reported interruptions to their MS care and limited access to COVID-19 testing, which may have been the cause of this increase. 19 Woo et al reported that patients after COVID-19 recovery presented with substantial neurocognitive deficits related to attention, short-term memory and concentration and language tasks. 20 However, their cognitive status remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on ofatumumab exhibited a significantly lower annualized relapse rate in both trials and the percentage of patients with disability worsening confirmed at 3 and 6 months was also significantly lower with ofatumumab compared to teriflunomide [ 72 ]. Ofatumumab bears the important advantage of being the first self-administered, B cell targeting DMT in MS, delivered via an autoinjector pen, enabling patients to self-administer the treatment at home, avoiding visits to the infusion center, a particularly relevant advantage during the current COVID-19 pandemic [ 187 ].…”
Section: Indications In Neurologymentioning
confidence: 99%
“…Stay-at-home orders and social distancing measures have limited in-person interactions with MS care teams and reduced access to health facilities for diagnosis and monitoring. Pandemic-related restrictions and patient concerns of potential infection outside of the home have led to gaps in clinical care, resulting in potential delayed disease evaluation, diagnosis, and monitoring as well as care for non-MS comorbidities ( Vogel et al., 2020 ). Access to critical rehabilitative care such as physical, occupational, and speech therapy has also been disrupted, impacting the holistic approach to patient support.…”
Section: The Multifaceted Impact Of the Pandemic On Ms Carementioning
confidence: 99%
“…Social distancing measures have limited in-person engagements with their social support networks, thereby potentially impacting their mental health ( Bhaskar et al., 2020 ). Mental wellbeing may be further compromised by financial concerns stemming from self-quarantining or job loss, and heightened fears about contracting COVID-19 ( Vogel et al., 2020 ). It is therefore important to ensure that PwMS receive the physical and psychosocial care needed to see them safely through the pandemic ( Figure 1 ).…”
Section: The Multifaceted Impact Of the Pandemic On Ms Carementioning
confidence: 99%